Markerless Augmented Reality (AR) pada Media Pembelajaran Pengenalan Komponen Transmisi Manual Mobil - Indriyani, Triska Widya; Suryanto, Agus (Jurusan Teknik Elektro Universitas Negeri Semarang, 2021)
Nowdays technology has developed very rapidly. Technological development that are currently being developed by many game developers and other applications, is Augmented Reality (AR). AR can be used as an alternative learning media, such as for the introduction of manual transmission components in cars. The study was aimed to develop a learning media application for the introduction of manual transmission components in cars and to test the feasibility of applications to support learning based on Markerless Augmented Reality. This application development method used SDLC or System Development Life Cycle software. The SDLC model that used in this study was the Waterfall model. SDLC consists of the planning, analysis, design, implementation, testing and maintenance. This reaction produced an AR application of Manual Car Transmission which contains material on the introduction of car manual transmission components. Testing applications included blackbox, media and material feasibility, and user response testing. The blackbox testing result got 100 %. The media feasibility analysis show that the assessment of media experts was 87,5 %, material expert 94,4 %, and user response was 85,47 %. From that the AR learning media application manual transmission of cars is categorized as â€œfeasibleâ€ to be used as learning media applications.